2012
DOI: 10.5304/jafscd.2012.031.011
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Economic Benefits of Agritourism: The Case of New Jersey

Abstract: Many small American farms struggle to remain economically viable due to a confluence of global market dynamics, rising costs, and urbanization pressure. Agritourism is an increasingly popular form of alternative agriculture enterprise development designed to expand farm income, generally through fuller employment of existing farm resources. The economic significance of agritourism within the farm community, however, is not well understood. Existing literature is inconclusive about the importance of agritourism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 33 publications
3
74
0
2
Order By: Relevance
“…Useful overviews of agritourism exist about the study area (Ainley & Smale, 2010;Stobbe et al, 2010;Tew & Barbieri, 2012 ) and about direct marketing of farm products (Park, Mishra, & Wozniak, 2014;Tippins, Rassuli, & Hollander, 2002). Schilling et al (2012) describe agritourism as a way for farmers to utilize all of the resources of their farms, and found that the large majority of agritourism activities occur on small farms such as those found in our study area as well. This paper adds some attention to the understudied intersection of these areas, exploring those operations that blend direct sales with agritourism.…”
Section: Farm Stores and Agritourismmentioning
confidence: 53%
“…Useful overviews of agritourism exist about the study area (Ainley & Smale, 2010;Stobbe et al, 2010;Tew & Barbieri, 2012 ) and about direct marketing of farm products (Park, Mishra, & Wozniak, 2014;Tippins, Rassuli, & Hollander, 2002). Schilling et al (2012) describe agritourism as a way for farmers to utilize all of the resources of their farms, and found that the large majority of agritourism activities occur on small farms such as those found in our study area as well. This paper adds some attention to the understudied intersection of these areas, exploring those operations that blend direct sales with agritourism.…”
Section: Farm Stores and Agritourismmentioning
confidence: 53%
“…It has been observed that agri tourism, specifically farm-based accommodations is a "minor contributor" to the incomes of farmers in southern Germany (Oppermann, 1995;Busby and Rendle, 2000). However, past research confirms that agri tourism development in USA and rest of the world is often motivated by socially, including fulfillment of personal entrepreneurial goals, education of the public about farming, and social interactions with guests (George et al, 2011;McGehee, et al, 2007;Nickerson et al, 2001;Schilling, et al, 2012;Sharply and Vass, 2006;Weaver and Fennell, 1997). However, improving farm income is generally a primary motive behind the development of agri tourism enterprises.…”
Section: Use Of Agri Tourism Products In Managing Risk In Farmingmentioning
confidence: 99%
“…The link identified in our study between owner satisfaction with his or her preservation experience and succession planning suggests the importance of understanding the types of incongruities that may exist between the views of owners and easement holders as to what uses are appropriate on preserved farmland. For example, agritourism and direct marketing are growing in importance, particularly in urbanizing areas (see Schilling, Sullivan & Komar, 2012). This growth is fueled in part by an expanding local food movement and by the economic necessities of a changing agricultural business climate.…”
Section: Policy Implications and Further Researchmentioning
confidence: 99%